As neurociências ao serviço da linguagem - Oliveira, Ana Maria Roza de Oliveira Henriques de (Linguarum Arena, 2018)
Human language, with the emergence of the Cognitive Sciences, contributes so decisively to the opening of the interdisciplinary area which is already transversely considered, the Neurosciences. All that concerns the processing of language information occupies now its own space in the exploitation and the interpretation of several ongoing processes, namely the acquisition and the learning, as well as processes involving injuries of the language. The brain is the center of interpretation which allows any researcher, from now on, to deepen and to understand the origin of such complex systems like, for example, reading and discourse. The present discussion should contribute to the debate of the theoretical and methodological foundations of language neuro-functional organization in the brain as well to the study of language teaching.